POPULASI AYAM HUTAN MERAH (Gallus gallus) DI KAWASAN HUTAN DESA TONUSUKECAMATAN PAMONA PUSALEMBA KABUPATEN POSO - Natalia, Rafika Anggelin; Naharuddin, Naharuddin; Rosyid, Abdul (Universitas Tadulako, 2020)
Red jungle chicken populations in various countries in Asia tend to decrease due to hunting and habitat degradation. However, the most important threat to the population of red jungle fowl is the occurrence of crossbreeding naturally, between red jungle fowl with domestic chickens that are not caged. The purpose of this study was to determine the population of red jungle fowl (Gallus gallus) located in the Forest Area of Tonusu Village, Pamona Pusalemba District, Poso Regency. This study uses a survey method which is done by direct observation in the field to get a general picture of the population density of red jungle fowl (Gallus gallus). Determine the point of observation by adjusting the hours of activity Red jungle fowl (Gallus gallus) with 4 observation points. Observations were made in the morning at 05.00 - 10.00 WITA and continued in the afternoon at 15.00 - 18.00 WITA at the designated point by repeating 5 times. The results of the study of the population of the Red Forest Chicken (Gallus gallus) in the village area of Tonusu, were divided into four observation points namely I, II, III and IV points and obtained a total of 11 red jungle fowls consisting of 7 male tails, 2 female tails, and 2 chicken tails. The average density of the four point counts is 0.04 head / ha. The differences in each observation point are due to several things that can affect the development of the life of red jungle fowl, especially supporting climatic conditions, feed components, water, protectors, as well as changes in environmental conditions caused by human activities such as illegal logging (illegal logging and forest conversion) and ongoing poaching activities.Keywords ; Red Forest Chicken population, Tonusu Village